Building Model of Flood Cases in Central Java Province using Geographically Weighted Regression (GWR) - Tuti Purwaningsih; Citra Saktian Prajaningrum; Mai Anugrahwati (International Journal of Applied Business and Information Systems, 2018)
Indonesia is one of the countries hit by many disasters. During the last five years the disaster increased in the last year, namely in 2016. In terms of the types of disasters, most were floods. The flood disaster has the highest incidence rate in Central Java Province. Flood is a natural phenomenon where there is excess water which is not accommodated by drainage in an area. To be able to identify the risk of flooding that affects humans and their environment, it is necessary to know the causes. The causes of flooding can come from natural and non-natural factors. Seeing the high incidence of flooding in Central Java, the authors drew attention to research whether the factors that influence flooding in the province and how to model it by looking at the spatial effects in it using Geographically Weighted Regression (GWR) analysis. The results showed that the incidence of flooding using GWR analysis had four significant variables, namely rainfall, rainy days, humidity and area. From the model obtained, it has R2 of 56%, and has as many as six models of variables that are significant for each region.